MADRASAH HEAD'S LEADERSHIP STRATEGY IN EMPOWERING THE COMMITTEE AT MADRASAH ALIYAH AL WASHLIYAH AEK KANOPAN - Susilo Siregar, Panji Pandu; Hanum, Azizah (JURNAL TARBIYAH, 2023)
This research aims to reveal the role of the committee at the Private Madrasah Aliyah Al Washliyah Aekknopan Kualuh Hulu North Labuhanbatu, the Madrasah Head's Program in empowering the committee at the Private Madrasah Aliyah Al Washliyah Aekknopan Kualuh Hulu North Labuhanbatu, Factors that influence the Head of the Madrasah in empowering the committee at Madrasah Aliyah Private Al Washliyah Aekknopan Kualuh Hulu North Labuhanbatu, the obstacles that the Madrasah Head feels in empowering the committee at the Al Washliyah Private Madrasah Aekknopan Kualuh Hulu North Labuhanbatu, and what solutions are provided by the Madrasah Head facing obstacles in empowering the Committee at the Private Al Washliyah Aekknopan Kualuh Aliyah Madrasah Upstream of North Labuhanbatu. This research uses a qualitative type of research, with a phenomenological approach, using data collection techniques in the form of observation, interviews and documentation studies. The results of this research revealed five findings, namely that the role of the committee at the Al Washliyah Aekknopan Kualuh Hulu Private Madrasah, North Labuhanbatu was not good enough because the Committee only waited for instructions from the madrasah, the program carried out by the Head of the Al Washliyah Aekknopan Kualuh Hulu Private Madrasah, North Labuhanbatu was sufficient. good, the influencing factors are the madrasah's need for a committee in accordance with existing regulations, and the opportunity to empower the committee, the obstacle for the Madrasah Head in empowering the Committee is because each party is busy and the Madrasah Committee does not provide their program because they are just waiting for instructions from the madrasah, and the solution to empowering the Committee is for each party to spend their time.